2021
DOI: 10.1002/anie.202104794
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrole Hemithioindigo Antimitotics with Near‐Quantitative Bidirectional Photoswitching that Photocontrol Cellular Microtubule Dynamics with Single‐Cell Precision**

Abstract: We report the first cellular application of the emerging near‐quantitative photoswitch pyrrole hemithioindigo, by rationally designing photopharmaceutical PHTub inhibitors of the cytoskeletal protein tubulin. PHTubs allow simultaneous visible‐light imaging and photoswitching in live cells, delivering cell‐precise photomodulation of microtubule dynamics, and photocontrol over cell cycle progression and cell death. This is the first acute use of a hemithioindigo photopharmaceutical for high‐spatiotemporal‐resolu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 62 publications
0
43
0
Order By: Relevance
“…Photoinduced geometry change in a hemithioindigo based molecular motor has been used to modulate catalytic efficiency of a chemical reaction [138] . Pyrrole hemithioindigo 57 has been employed in the photocontrol of cellular microtubule dynamics and cell cycle progression and cell death [139] …”
Section: Different Classes Of Visible Light‐driven Molecular Switches...mentioning
confidence: 99%
See 1 more Smart Citation
“…Photoinduced geometry change in a hemithioindigo based molecular motor has been used to modulate catalytic efficiency of a chemical reaction [138] . Pyrrole hemithioindigo 57 has been employed in the photocontrol of cellular microtubule dynamics and cell cycle progression and cell death [139] …”
Section: Different Classes Of Visible Light‐driven Molecular Switches...mentioning
confidence: 99%
“…[138] Pyrrole hemithioindigo 57 has been employed in the photocontrol of cellular microtubule dynamics and cell cycle progression and cell death. [139]…”
Section: Hemithioindigos and Iminothioindoxylsmentioning
confidence: 99%
“…In subsequent studies, Sailer et al implemented near-quantitative photoswitchable pyrrole HPIs to address two additional factors that limit the photoswitchability of azobenzenes in biological assays: the limited bidirectional photoisomerization within the biologically compatible light spectrum and the restricted accessibility of high photostationary states due to fixed-wavelength lasers available in confocal microscopes [ 44 ].…”
Section: Photoswitchable Microtubule-targeting Agentsmentioning
confidence: 99%
“…Remarkably, they also demonstrated that during confocal microscopy this compound can be photoactivated in live cells with spatial and temporal precision. Whereas microtubule dynamics were not significantly influenced by the addition of the Z -isomer, irradiation with 442 nm laser pulses resulted in suppressed microtubule dynamics [ 44 ].…”
Section: Photoswitchable Microtubule-targeting Agentsmentioning
confidence: 99%
“…These compounds, which are cell-compatible and show antimitotic photoswitchable bioactivity, have been named hemithioindigo-colchicinoid tubulin binders (HOTubs, 450 nm) ( Sailer et al, 2019 ). Likewise, the microtubule inhibitor colchicine served as template for the design of pyrrole hemithioindigo (PHTubs) compounds (photoswitched in the range 435–450 nm) ( Sailer et al, 2021 ). Furthermore, colchicine has been used as structural reference for the development of photoswitchable cytotoxic compounds based on spiropyran (SP, exposed to UV light at 365 nm) ( Rastogi et al, 2021 ).…”
Section: Photopharmacology: Light-triggered Analogues Of Mta Smentioning
confidence: 99%